PENGARUH MINAT DAN MOTIVASI BELAJAR PESERTA DIDIK TERHADAP HASIL BELAJAR PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN (PJOK) KELAS 2 SD KRISTEN BETHEL SURABAYA - Nathaniel Andrian Nico Pradhana; Atiqoh; Rohman, Ujang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Physical Education, Sports, and Health (PJOK) is an integral part of the education curriculum to advance students' physical and mental health. However, many students have not achieved maximum results in the Physical Education learning process. Interest and level of learning motivation have an important role in determining learning outcomes. This research aims to determine the influence of students' interest and learning motivation on PJOK learning outcomes at the elementary school level. The research method used is descriptive research with a quantitative approach. The population in this study were all students of Bethel Christian Elementary School Surabaya. The sample was obtained using purposive sampling technique of 29 students from grade 2 of Bethel Christian Elementary School Surabaya Data collection was carried out by administering questionnaires and tests. Data analysis was conducted using the SPSS program consisting of data analysis requirements tests and hypothesis tests. Hypothesis testing uses the liener regression test. The research results show that there is a linear relationship between students' learning interest and learning motivation and PJOK learning outcomes. Thus, it can be concluded that there is a significant influence between students' interest and learning motivation on PJOK learning outcomes at Bethel Christian Elementary School, Surabaya.